Culture conditions antagonize lineage-promoting signaling in the mouse blastocyst. Issue 1 (July 2020) - Frum, Tristan; Ralston, Amy
Abstract : The mouse preimplantation embryo is a paradigm for discovery of the molecular principles governing formation of specific cell types during development. In this Point of View Article, we show that conditions commonly used for ex vivo culture of preimplantation development are themselves antagonistic to a pathway that is critical for blastocyst lineage commitment.